Análisis del comportamiento del hormigón reforzado con fibras metálicas para el ensayo de flexo-tracción - Campoverde Cajamarca, Darwin Fabián (2017)
The composite material called concrete is preferred in most civil constructions because of its high compressive strength and long life but due to many disadvantages that this material presents, we are in the need to look for ways to reinforce it and satisfy solicitations of loads to which the concrete alone can not withstand. It is for this reason that this work has analyzed the behavior of the metal fibers in the concrete compared to the flexotraction test. For the current work of the titulación has used the Dramix metallic fibers of the series 3D 45/30 BG to those that correspond to length of 30 millimeters and diameter of 0.62 mm. These fibers have a tensile strength of 1270 N / mm2 according to the supplier and manufactured according to ASTM A820. The concrete mix was prepared following the general specifications for the construction of roads and bridges proposed by MOP-001-F 2002. A quantity of 25 kg fibers per cubic meter of the mixture was used using the mixing methodology suggested by the ASTM C 1116 standard for fiber reinforced concrete. This work has been directed to the study of the behavior of concrete reinforced with the metallic fibers that a being used in a standard industrial floor by a we do not interest the behavior that the metallic fibers have in this type of rigid pavement, reason why has designed with a compressive strength at 28 days of curing of 21 MPa. The results obtained in the compression tests at 7 days of age of the simple concrete specimens present a percentage of 70% with respect to the designed strength of 21 MPa and those that are contaminated with the fiber reinforcement present 77% of the same, this shows that the inclusion of fiber genera a 7% increase in the compressive strength in the first 7 days of curing. The same percentage of increase was reflected in the 14 and 21 days of age. At 14 days, 89% in the elements without fibers and 96% in the cylinders with fibers. At 21 days of age, the unreinforced specimens had an average of 25.81 MPa and the reinforced specimens averaged 27.36 MPa, with an increase of 6%. The non-reinforced test specimens tested with indirect tensile strength had a mean strength of 3.64 MPa and those with a fiber reinforcement of 3.71 MPa, reflecting a 2% increase in tensile strength and a rather significant improvement in the ductility since at the moment of receiving the last load the reinforced specimens were not divided in diametral form thanks to the action of the metallic fibers which served as bridge between both parts of the crack. In the unreinforced beams a value of 3.78 MPa was obtained in its average breaking modulus and 4.69 MPa for the reinforced ones, thus having an increase of 24% thanks to the action of the fibers, as well as in the indirect tensile tests here also a strong increase in the ductility of the specimens was observed since once the crack was generated, the beams continued to withstand loading up to about 10MPa in average breaking moment. As conclusion of this work we have a correlation between the values of indirect tensile strength and rupture modules, obtaining expressions that serve to leave aside the control of rupture modules by the flexotraction test and start using the tensile test indirect test of cylindrical specimens, which prove to be simpler to elaborate and to manipulate in relation to the beams, due to the great volume that they present. With the percentages of increment of specimens with and without metallic fibers in indirect tensile strength, compressive strength and modulus of rupture, it has been demonstrated that for elements subjected to bending, the use of metallic fibers in the concrete mixture represents a significant improvement. It was also observed that elements not reinforced with metallic fibers had a fragile failure in contrast to those that were reinforced, which presented a ductile failure since at the moment of the crack they underwent a marked deformation first, before reaching the failure.